Brushite (Ca, M)HPO4, 2H2O doping with bioactive ions (M = Mg2+, Sr2+, Zn2+, Cu2+, and Ag+): a new path to functional biomaterials?. (June 2020) - Sayahi, M.; Santos, J.; El-Feki, H.; Charvillat, C.; Bosc, F.; Karacan, I.; Milthorpe, B.; Drouet, C.
Abstract: Dicalcium phosphate dihydrate, DCPD (CaHPO4 ·2H2 O), brushite, is an important calcium phosphate compound encountered in mineralized tissues and used in medicine, especially in bone cement formulations. However, the use of DCPD as direct implantable biomaterial has not received dedicated attention. In addition, the possibility to dope DCPD with biologically active ions to modulate its performances was not systematically explored. We have investigated in depth the doping of DCPD with Mg 2+, Sr 2+, Zn 2+, Cu 2+, and Ag + ions. Clear modifications in terms of chemical composition, particle size, pore distribution, crystal morphology, and affinity for water were pointed out. Then, the samples were cultured with human adipose-derived stem cells to explore cytotoxicity and proliferation. Various behaviors were noticed dependent on the incorporated metal ions. Such DCPD compounds associated with bioactive metal ions, and particularly Ag + and Zn 2+, appear promising as a new family of reactive materials for use, as such or in combination, in bone-related applications. Highlights: Brushite (dicalcium phosphate dihydrate [DCPD]) doped with 5 biologically relevant ions was investigated. Several characters of precipitated crystals are noticeably modified upon doping. Crystal morphology, particle size, pore distribution, and affinity for water are modified. Cytotoxicity and proliferation was explored in vitro. DCPD doped with Ag + and Zn 2+ are promising as new reactive compounds.